ANALISIS STRUKTUR VEGETASI KAWASAN SEMPADAN PANTAI DI KABUPATEN BANGKA TENGAH - Nelawati Nelawati; Anggraeni Anggraeni; Irma Akhrianti (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2020)
Mangrove forests and coastal forests are coastal green lines that have ecological and economic functions. This study aims to determine the types, composition and structure of coastal border vegetation in Central Bangka Regency. The method of observing and collecting vegetation data uses the transect line and plot method. The results of the inventory of coastal border vegetation at 3 research stations found 803 individuals, 33 species and 22 families. Coastal vegetation types found in Station I were 12 species, Station II were 8 species and Station III were 25 species. The type of vegetation that has the highest INP value at the tree level is Sonneratia caseolaris (L.) Engl. and Pandanus tectorius Parkinson ex Z. of 300.00%, at the pole level, Vitex pinnata L. of 300.00%, at the stake level, Sonneratia caseolaris (L.) Engl. and Vitex pinnata L. of 200.00% and at the seedling level, Sonneratia caseolaris (L.) Engl. and Rhizophora apiculata BI. of 200.00%. The highest diversity index is at station III, 4.4, which is classified as high category. The highest dominance index is at station II, 0.5 which is classified as medium category. The highest evenness index is found in station III, 0.8 which is classified as high category.